The Impact of Sporting Events on Air Pollution: An Empirical Examination of National Football League Games - Nicholas Watanabe (19450285) (2023)
Background Prior research has found that large-scale sporting events may potentially impose negative consequences on the environment, thus impeding the sustainability goals of the sport industry. Along these lines, the current study extends the literature by examining the impact that National Football League (NFL) games have on local-area air pollution. (2) Methods: Air Quality Index (AQI) data measuring six major forms of air pollution were gathered from air monitors positioned close to NFL stadiums and matched with the number of attendees at games. From this, multiple regression analysis was utilized to estimate whether the number of fans was related to changes in air pollution. (3) Results: The regression models found that Ozone and Nitrogen Dioxide levels increased as more individuals attended NFL games. Additional robustness checks and falsification tests suggest that the average NFL event results in an approximately two-percent increase in Ozone levels. (4) Conclusions: The findings from this study contribute to the literature by providing evidence that highly attended sporting events increase pollution levels in the areas near stadiums. Thus, governments and sport organizations should consider low-emission methods to get fans to travel to games in order to reduce their environmental impact. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su15065568